THE PRINCIPLES OF SEPARATE ACCOUNTING OF COSTS AND REVENUES FROM THE PRACTICE OF JSC "SO UES" - I. Bardina; D. Blyablina (Вестник университета, 2016)
In the article we consider a system of separate accounting in the electricity sector. The result of the work is the consideration of the positive and negative aspects of such innovations in the selected segment of the economy, specifically in the enterprise, indicated as an example according to the specifics and data on his work. On the issues identified will be offered solutions.